Evaluation of endothelial function and skin microcirculation in the early phase of chronic inflammation in inflammatory arthritis - Klimek, Ewa (2017)
Objective: Assessment of endothelial function, skin microcirculation, subclinical atherosclerosis and immune response, in the early stage of chronic inflammation, with respect to inflammation, disease activity and cardiovascular (CV) risk factors. Methods: In patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) of short duration untreated with disease-modifying antirheumatic drugs and in healthy subjects, CV risk factors, blood biochemical parameters, flow cytometry, laser Doppler flowmetry and intima-media thickness (IMT) in carotid artery ultrasonography were assessed.Results: Compared to controls RA patients presented: 1) higher endothelial activation markers dependent on inflammation and at the same time independent of disease activity, 2) monocytosis and shifts in monocyte subpopulations, 3) changes in expression of monocyte activation markers also with respect to disease activity, 4) altered skin microvascular function dependent on inflammation (also in AS), 5) similar CV risk profile (also in AS) and IMT. Conclusions: In the early stage of chronic inflammation, disease activity and inflammation are related to endothelial activation, altered skin microvascular function and impaired functional monocytic properties, accompanied by a similar CV profile and lack of subclinical atherosclerosis. There may be other mechanisms governing endothelial activation.
Keywords: rheumatoid arthritis; ankylosing spondylitis; endothelial activation; microcirculation; monocyte subpopulations